The Development of Malunggay (Moringa oliefera) Molo Wrapper: Techno-Guide for Instruction, Community Extension, and Production - John Vincent I. Manalo (RES MILITARIS, 2023)
This experimental study was conducted to formulate a Molo Wrapper enhanced with Malunggay leaves in three (3) different treatments for three replications. The treatment formulations and composition were based on the standard and basic ingredients and procedures of making Molo Wrapper. There are three (3) levels of moringa powder added to the basic recipe. Treatment 1 (T1): one half (1/2) cup of moringa powder; Treatment 2 (T2): one (1) cup of moringa powder; and Treatment 3 (T3): two (2) cups of moringa powder. The sensory evaluation was performed using the researcher-made score sheet designed for the nine-point hedonic rating scale tests. The data were statistically analyzed. The findings revealed that T1 and T2 formulations containing a lesser amount of moringa powder have higher acceptable descriptions of like very much. Moringa powder is acceptable and can be used as an additive in developing Molo Wrapper as a new food product innovation derived from sensory analysis. Consumer panelists are more sensitive to the sensory quality that may have affected their general acceptability of the product than the experts because of the unusual color, appearance, and texture caused by Moringa powder. The developed acceptable treatment will be introduced as a techno-guide for instruction, extension services, and production.